Modelagem gravimétrica da Bacia de Taubaté-vale do Rio Paraíba do Sul, leste do estado de São Paulo - Fernandes, Flávio Luís [UNESP]; Chang, Hung Kiang [UNESP] (FapUNIFESP (SciELO), 2001)
This paper presents the gravity survey refinement of the Paraíba do Sul river valley, east region of São Paulo state, by acquisition of 646 gravity stations. Further than the traditional Free-Air and Bouguer corrections, it was necessary to apply the Terrain Correction due the proximity of the Mantiqueira and Mar mountain ranges. An enhanced understanding of Taubaté Basin structural framework was the main objetive of this work. As result, we present the Bouguer Gravity Map of the east region of São Paulo State and the Residual Bouguer Gravity Map generated by Upward Continuation and High-pass filtering. The 2D Gravity Modeling was applied in 4 sections, using bi-dimensional models for the bodies that produced the anomalies (Talwani Method). After integrating the gravity data with the interpretation of 11 seismic sections, it was possible to delineate the Taubate Basin structural framework, which shows an utmost sedimentary thickness of 800 m in the depocenters. It was also interpreted an ultramaphic alkaline plug in the subsurface of Caçapava city.
Gravity modeling of Taubaté Basin-Paraíba do Sul river valley, east of São Paulo state
Keywords: Bouguer Gravity Map; Gravity; Modeling; Taubaté Basin; Bouguer anomaly; gravity survey; Brazil; Sao Paulo [Brazil]; South America